Branding Design of the Indonesian Islamic Museum K.H. Hasyim Asy’ari in Strengthening the Museum’s Brand Image - Maulidia, Suci; Kusuma, Bilqis Hilda; Puspitadewi, Ganis Chandra; Adytya, Rifqi (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: The KH Hasyim Asyari Islamic Museum (MINHA) in Jombang is dedicated to honoring KH Hasyim Asyari and preserving historical artifacts related to Nahdlatul Ulama. Although it opened in 2018, the museum faced closure due to the pandemic until 2022, and local visitor numbers remain lower compared to those from outside the city.Objective: This research aims to design a branding strategy to strengthen MINHA's image.Methods: The methodology follows the stages of Moilanen and Rainisto: (1) Start-up and Organization, (2) Research Stage, (3) Forming Brand Identity, (4) Making, Executing, and Enforcing the Plan, (5) Implementation and Follow-up.Results: Findings reveal strengths in historical heritage and strategic location, but weaknesses in visitor data and promotion. The proposed branding strategy includes developing a travel profile book, Instagram feed, billboard, brochures, and merchandise.Conclusion: The study concludes that branding design following the Moilanen and Rainisto methodology is expected to enhance the potential of historical tourism and increase public awareness of cultural heritage.